Role of optical rectification in photon-assisted tunneling current - Pierre Février; Julien Basset; Jérôme Estève; Marco Aprili; Julien Gabelli (Communications Physics, 2023)
Optical rectification describes a nonlinear optical process that can be exploited by nanoantennas to convert optical radiation to a DC voltage, acting as a type of detector. Here, the authors consider optical rectification in a metallic tunnel junction, finding that current theory cannot account for experimental results on photon-assisted tunneling under infrared illumination, unless temperature effects are included.